The Role of Access Capacity of Business Actors in the “New Normal” Policy Congruence in Indonesia - Wasisto, Aryo; Lisnawati, Lisnawati (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
In reducing the number of COVID-19 transmissions, the Government of Indonesia implemented a three-month social restriction policy. The social restriction caused shocks in the economic sector. This article analyzes the motivational factors that enable business people in Indonesia who are members of business organizations to use political party access and congruence to accelerate the "new normal" policy. The access capacity is related to business people's ability to reach political parties, while congruence can be seen from the level of their acceptance of policy outputs. This study develops a variable of access capacity consisting of political party membership, company scales, and the type of business organization. Data was gathered through an online survey using Google Forms to 147 business actors who are members of the national business group. By using logistic regression analysis at the individual level, we find that the scale of the company owned by a businessperson significantly influences her/his ability to access political party rather than passively following organizational policies. The company scale variable also considerably affects the acceptance of the "new normal" policy. Businessman membership in political parties only affects access capacity, but not policy congruence. In the context of COVID-19 in Indonesia, the increasing losses have an impact on accepting the "new normal" policy. This finding indicates that in general: only large companies owners can directly lobby their political representatives; pandemic, as a crisis situation, is an exception to produce congruent policies; capital is still the most powerful modality in the policy; and COVID-19 has had a significant impact on business people's incongruence with the "new normal" policy